INVERSI DATA VERTICAL ELECTRICAL SOUNDING (VES) KONFIGURASI SCHLUMBERGER DI KAMPUNG NAMBON KABUPATEN JAYAPURA MENGGUKAN METODE FIXED-WIDTH THICKNESS DAN METROPOLIS SIMULATED ANNEALING - Anike Bowaire; Zakaria Victor Kareth (Jurnal Natural, 2023)
A Research of inversion of Vertical Electrical Sounding (VES) data of Schlumberger configuration using combination of Simulated Annealing (SA) dan Fixed-Width Thickness methods has been carried out. The fixed-width thickness method was used to objectively determine the number of subsurface layers. The SA method was used because it is stable and the initial model does not have to be at proximity of the actual solution. The inversion results on synthetic data of 3 and 4 layers show a good fit between the sintetik data and inverted model. In addition to the number of layers, the fixed-width thickness method also provides information on the range of depth and resistivity values for each layer whit can be used as input for inversion. The inversion results on synthetic data containing 20% noise indicating that the model and data have a good fit. The level of fit of the method depends on the number of model parameters and the error tolerance. The inversion results on field data in Nambon village, Jayapura district, show that there are 5 subsurface layers. The geological interpretation of these five layers is that the first layer is the top soil layer which is weathered limestone, clay and sand. The second, fourth and fifth layers are limestone of the Jayapura formation (Qpj) with a resistivity range between 923 – 5881 Ωm. The third layer is karst, which may contain groundwater, formed in the limestone of the Jayapura formation.